The Relationship between a Western Amazonian Society and Domesticated Sedges (Cyperus spp.) - Kujawska, Monika (2020)
The article discusses the relationships between the Ashaninka people from Peruvian Amazonia and the domesticated sedges (Cyperus spp.) cultivated in almost every Ashaninka home garden, and mostly exchanged within family circles. An over-differentiation phenomenon is observed, in which four species of Cyperus correspond to 86 folk species. The names of folk species are formed by secondary lexemes, composed of a semantically active constituent and a generic suffix (i)benki. The names contain mnemonic cues to differentiate otherwise morphologically similar plants, and their meanings correspond to Ashaninka ontological categories, thus revealing many levels of connectivity between them and non-humans. The wide scope of specific uses (approx. 60 registered) assigned to Cyperus spp. is only partly supported by phytochemicals and ergot alkaloids in the fungus-infested sedges. The key to understanding the ibenki?s (Cyperus) agency lies in local cosmologies, in which domesticated sedges are viewed as plant-persons and kin. The Ashaninka are engaged in producing the bodies of their kin, the ibenki. Simultaneously, ibenki are powerful allies in restoring harmonious social relations and protecting people against the intentional actions of other humans and non-humans.